Accessing the NDIS - Assisting people with psychosocial disability to access the NDIS: a guide for Commonwealth-funded community mental health service providers. - Masters, Stacey; Shelby-James, Tania (Australian Government, 2017)
The practice guide has been developed to assist Commonwealth-funded community mental health and carer respite program providers in supporting participants to access the National Disability Insurance Scheme (NDIS).